The Future Speaks: Exploring Artificial Intelligence’s Impact on EFL Students’ Speaking Skills - Delis Meta Tiana; Dwi Puji Hastuti; Retno Rahayuningsih (Universitas Islam Negeri Palopo, 2025)
This research explores the influence of the Artificial Intelligence: Fully Fluent application on Indonesian junior high school students’ English-speaking skills and explores teacher and student perceptions of its use. The study employed a mixed method using interviews and questionnaires with teachers and students to get qualitative data alongside quantitative data from a quasi-experiment pre-posttest. Teachers reported that the application developed motivation, confidence, and behavioral engagement in class, with student surveys being overwhelmingly positive with convenience, enjoyment, and increased confidence. Regarding quantitative results, statistically significant improvement is reported since the experimental group's mean scores (84.51) are greater than the control group's (71.91). In both the independent samples t-test (Sig= 0.000 < 0.05) and paired samples t-test (Sig= 0.000 < 0.05), there are statistically significant differences, which reflect the effect of Fully Fluent. These results indicate that AI-based tools like Fully Fluent can enhance oral proficiency and foster positive learning attitudes. Practically, the findings suggest that AI speaking applications be used as supportive tools to enhance EFL instruction and build learner confidence in authentic communication.